Anti-Arcing DC Circuit Breaker for High Payload Drone Application - Rosli, Nabil Fikri; Mohd Ariff, Mohd Aifaa (Evolution in Electrical and Electronic Engineering, 2022)
his project discusses the development of an anti-arcing DC circuit breaker for high-payload drone applications. For a heavy-lift drone, there is a common issue of arcing and high current during the operation because the circuit is highly capacitive. In order to address this issue, the anti-arcing DC circuit breaker is proposed in this project. First, the circuit breaker is designed and simulated using the MULTISIM software. Then, the performance of the circuit breaker is evaluated under various operating conditions. Next, the printed circuit board of the circuit breaker is designed using the ULTIBOARD software. From the simulation, it is observed that the circuit breaker is able to limit the inrush current to the speed controller circuit during the circuit-making process. On the other hand, the circuit is able to withstand the high current flow during normal operating conditions. The result implies that the proposed anti-arcing DC circuit breaker is able to reduce the arcing during the circuit-making process while withstanding a huge current flow during normal operating conditions. The performance of the proposed circuit breaker is crucial for a heavy-lift drone to ensure that the operator does not expose to an arc during operation